The Role of Digital Media Against Zakat Fundraising in The Perspective of Sharia Economic Law (Research Study at the IZI Institute) - Wahyudi, Wahyudi; Hidayat, Hidayat; Kholid, Hendra (Jurnal Indonesia Sosial Sains, 2024)
This study explores the use of digital media for zakat fundraising at IZI, explains its implementation within the framework of Sharia economic law, and its impact on increasing zakat collection. IZI's approach to digital media-based zakat fundraising is not only interesting but also educational and diverse. The purpose of this study is to investigate and analyze the strategy and effectiveness of using digital media in collecting zakat funds by zakat institutions, focusing on the Indonesian Zakat Initiative (IZI). Methodologically, the study used a variety of techniques, including interviews with relevant personnel at IZI, literature review within the institution, direct observation of zakat contributors to IZI, and qualitative analysis through graphical representation of zakat collections over time. This method is carried out meticulously in collaboration with IZI staff to ensure data accuracy. The result of this study is that the adoption of zakat fundraising through digital media at IZI has proven effective and diverse. Collaboration with Tokopedia through "zakatpedia" has helped increase the zakat collection significantly. Fundraising through digital media by Sharia principles provided that it does not harm other parties, supported by references to the Quran, Hadith, Ijma', Qiyas, and Fatwa DSN MUI, and the role of digital media-based fundraising in IZI has become a key factor in collecting zakat. This is evidenced by the consistent increase in zakat collection, an average of 20% per year since the adoption of digital media. In conclusion, it is important to embrace digital platforms for zakat fundraising within the scope of the Islamic economy. The innovative approach taken by IZI not only enhances zakat collection but also upholds the ethical and legal principles integral to Islamic finance.